Association Between Physical Activity and the Incidence of Knee Osteoarthritis Among Elderly Individuals- a Cross Sectional Study - Nimra Iftikhar, Yasir Mustafa, Zainab Nasrullah, Aqsa Anwar, Khurram Shahzad, Muhammad Kaleem, Asad Ejaz, Adnan Hashim, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Physical activity has been linked to a number of health benefits, including a decreased chance of developing long-term conditions like diabetes, heart disease, and obesity. However, there has been some concern that some exercise types, particularly those that involve high impact or repetitive movements, may increase the risk of knee osteoarthritis (OA) in older people. Methodology: This study was conducted using a cross-sectional design to explore the connection between physical activity and knee osteoarthritis in elderly individuals. The participants were carefully chosen from community centers, senior centers, and healthcare facilities, and all were 65 years old or above. We made sure to use reliable methods such as the SF 36 Questionnaire and KOOS for Osteoarthritis to assess their physical activity levels. Results: This study involved 152 patients with knee osteoarthritis, with 39.5% being males and 60.5% females. The mean age was 70±3 years. The severity of knee problems was extreme in 24.3%, moderate in 49.3%, and no knee problems in 26.3%. Health status was poor in 28.9%, moderate in 46.7%, and good in 24.3%. There is a statistically significant association between health status and osteoarthritis as shown by the chi-square test with a p-value of 0.00, which is less than 0.05. Practical Implication: The results of this study have significant ramifications for public health initiatives that support weight control and physical activity promotion as ways to shield the elderly population from knee osteoarthritis. Conclusion: The study concludes that regular physical activity and maintaining a healthy weight can decrease the risk of knee osteoarthritis among elderly individuals. The implications of these findings suggest that public health policies should focus on promoting physical activity and weight management in preventing knee osteoarthritis in the elderly population. Keywords: physical activity, knee osteoarthritis, elderly individuals, incidence, association, prevention strategies.